Congenital cytomegalovirus infection: predisposing maternal factors. Issue 3 (September 1986) - Preece, P M; Tookey, P; Ades, A; Peckham, C S
Abstract : In a prospective study of cytomegalovirus (CMV) infection in pregnancy 69 congenitally infected infants were identified. The age, race, marital status, social class, and parity of the mothers of congenital CMV infants were compared with those of the screened population of women with non-infected infants. These factors were all individually strongly associated with the prevalence of congenital CMV. However, once age, marital status, and race were accounted for, neither social class nor parity had any additional effect. The overall congenital CMV rate was 3 per 1000 livebirths, ranging from 25/1000 for single black women under 20 to 1.6/1000 in married or cohabitating white women over 25.